Serat Weda Raga Karya R. Ng. Ranggawarsita : Suntingan Teks, Terjemahan dan Kajian Arkeologi â Genealogi Michel Foucault - , Teguh Tri Wahyudi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research has aim for philology, archeology of knowledge and genealogy of Michel Foucault towards Serat Wedaraga by R. Ng Ranggawarsita. This text contains procedure of ascending mystical practices for the doers in Javanese cultural tradition. There is certain assessment toward these practices, which leads to disorder and who went astray, become the main reason for this research. In philology studies, there are four available and readable manuscripts which contain Serat Wedaraga text. Two manuscripts are from Sana Budaya museum library, one manuscript is from Pura Pakualaman library and another book is published by Djojobojo in 1963. The purpose of this research is to create transliteration and translation in Indonesian, and then continued with analyzi ng the discourse within the text. The method of philology has some relevances to be applied in this research, considering the Serat Wedaraga text has endured transmission processes which effect the change of text. Through this method, one manuscript will be selected â among the fourth manuscript â as the basic study and transliteration. Manuscript PB. C. 108 collection in Sana Budaya Museum Library Yogyakarta is chosen as the basic manuscript because of the good condition, contains complete text, the writing is neat and readable, and appropriate metre principle. So the reader will understand to follow the written text in the manuscript, presented the diplomatic transliteration for the fourth manuscript, it include the translation in Indonesian. However to help the reader to understand the text substance, it is also presented the critical transliteration with appropriate formal Javanese grammar. Other than that this research also re-proved the Robson thought that Javanese texts always periodically develop and change (1981), so it is possible for texts in nineteenth century containing the thought of Islamic teaching and still record the traces of Hindhuism â Budhism thought, also the remains of animismdynamism believes. Therefore, with the approach of archeology and genealogy from Foucault, things about the ascending mystical practices which being discoursed in Javanese texts, especially Serat Wedaraga text, has became the focus of the analysis in this thesis. Other sources are used to support the analysis and conclusion toward the Serat Wedaraga text, just as other Javanese Islamic texts which have been transliterated and discussed by other previous researchers. In addition it is also supported by other books or literatures which connected with the focus of this research.